'We're Worth What We Are Paid': Unravelling the 'Paradox of the Contented Female Worker'. (September 2020) - Smith, Maria
Pay satisfaction research has suggested that women are more satisfied with their pay than men, even though, in general, women earn less. This article argues that this body of research has misconceptualised this phenomenon as an issue of women only. It also argues that previous explanations for this gender pay paradox have not adequately explained these patterns of satisfaction. A social constructionist approach to pay satisfaction is proposed which situates satisfaction within the context of structural inequality. This draws upon the scholarly work of feminist scholars and the conceptual ideas of Pierre Bourdieu. This theoretical approach is explored with data from qualitative interviews with support staff at universities in the United Kingdom. This evidence suggests that their pay satisfaction is influenced by beliefs about the 'value' of different occupations.